A Novel Biosorbent Lagenaria vulgaris Shell ‐ ZrO2 for the Removal of Textile Dye From Water. (1st July 2015) - Petrović, Milica M.; Radović, Miljana D.; Kostić, Miloš M.; Mitrović, Jelena Z.; Bojić, Danijela V.; Zarubica, Aleksandra R.; Bojić, Aleksandar Lj.
ABSTRACT: : A new biosorbent, abbreviated as LVB‐ZrO2, was synthesized by chemically modifying Lagenaria vulgaris shell with ZrO2 . The removal of textile dye RB19 from aqueous solution by LVB‐ZrO2 was studied. Characterization by SEM, FTIR and XRD confirmed the chemical modification of the biomaterial, which showed significant improvement of removal efficiency compared with unmodified Lagenaria vulgaris shell. LVB‐ZrO2 point of zero charge is 5.49. The biosorption process is highly pH dependent and the optimal pH is 2.0, at which complete dye removal was attained. The results are the best by a pseudo‐second order kinetic model. The optimal adsorbent dosage is 4 mg/dm 3 .The RB19 biosorption follows the Langmuir isotherm model ( R 2 =0.9978), with the maximum sorption capacity of 75.12 mg/g. LVB‐ZrO2 is a mechanically stable, easy to synthesize, cost‐effective, biocompatible and environmentally‐friendly biosorbent with the high potential for the removal of RB19 from aqueous solution.